Social movements: A force in contemporary world politics - NGUYỄN VIẾT THẢO (Political Theory Journal, 2026)
In contemporary world politics, particularly from the late 20th century to the present, social movements and popular movements have been asserting their roles as non-state actors with extensive mobilization of forces, exerting an increasingly powerful impact on the international landscape. The article analyzes the manifestations, operation methods, and core socio-political contributions of these movements over the past years. Besides, it identifies the challenges and constraints they face within the current context of globalization and geopolitical competition. The article is a research product of the Project KX.06.08/21-30: “Research on people-to-people diplomacy activities in the world within the new context and solutions for Vietnam”.